Preparation and characterisation of MgO nanoparticle incorporated bioresin using palm oil - Gan, Wei Teng (2017)
Alkyd resins are the product derivation of polyacid and polyol modified with monobasic fatty acid through polycondensation. Over the recent years, alkyd resins are widely used as the binder for composite and film-forming agent in paints. Vegetable oils were being explored and evaluated to synthesis alkyd resin due to its biodegradability and renewability. Synthesis of alkyd resins involved the alcoholysis of the oil by the polyol (commonly glycerol) and followed by polyesterification with a polyacid (commonly phthalic anhydride). Generally, a homogeneous or heterogeneous base catalyst was used to carry out the reaction. Nanoparticles were said to be a promising catalyst and colloidal form of nanoparticles was discovered in this context. In this work, palm oil based alkyd resin was synthesized over Magnesium Oxide (MgO) nano sol. Colloidal MgO nanoparticles were synthesised in glycerol and subsequently was used in alkyd resin synthesis. The alcoholysis process was conducted in the presence of various concentration of MgO (0.01, 0.02, 0.04 and 0.06wt% w.r.t. palm oil) at 240oC. The monoglycerides yield was found to achieve up to 95% in 40 minutes reaction time for 0.04wt% MgO catalysed system. As for the polyesterification process, fusion method was used since it was seldom discovered by other researchers. The crystallized size of the nanoparticle in sol was analysed by X-ray diffraction technique (XRD). Formation of the alkyd resin was monitored by measuring the acid values at different reaction time. Alkyd resins obtained after polyesterification of the alcoholysis products with phthalic anhydride at 240oC were characterized by employing Fourier Transform Infrared (FTIR) and Nuclear magnetic resonance (NMR) spectroscopy. The antimicrobial activity of MgO incorporated alkyd resin against microorganisms was tested via the Kirby–Bauer method. The MgO incorporated in alkyd resin not only reduced the reaction time but also was also proved to be an effective antibacterial agent which added value to the alkyd resin synthesised. Overall, MgO nanoparticles incorporated alkyd resin showed outstanding performance compared to conventional homogeneous base catalyzed system.